ChemInform Abstract: Synthesis and Characterization of Vanadium‐Doped LiMnPO4‐Compounds: LiMn(PO4)x(VO4)1‐x (0.8 ≤ x 1.0). Issue 12 (14th March 2013) - Clemens, Oliver; Bauer, Matthias; Haberkorn, Robert; Springborg, Michael; Beck, Horst Philipp
Abstract The title compounds are prepared by reacting ball milled stoichiometric mixtures of LiMnPO4 and LiMnVO4 twice at 850 °C under flowing Ar.